High and normal oleic runner‐type peanut cultivar by year effects on seed germination and vigor response to temperature. (27th July 2022) - Hurdle, Nicholas L.; Grey, Timothy L.; Branch, William D.; Monfort, W. Scott
Abstract: Experiments conducted from 2013 to 2018 evaluated the cultivar by year effects on breeder seed germination and vigor of five high oleic (HO) and five normal oleic (NO) runner‐type peanut ( Arachis hypogaea L.) cultivars grown under similar production practices. Seed germination and vigor were evaluated using a thermal gradient at temperatures of 12–36 °C (1.0 °C increments) over 7 d, and included growing degree day (GDD) accumulation. Germination across 6 yr of seed testing over all temperatures were phenotypically similar for HO's: Florida‐07 (59–86%), FloRun 107 (71–85%), Georgia‐09B (73–87%), Georgia‐14N (58–79%), Georgia‐13M (72–88%) and NO's: Georgia‐06G (65–88%), Georgia Greener (65–86%), Tifguard (65–85%), Georgia‐12Y (61–83%), and Georgia‐07W (60–91%). Lorentzian distribution models established the temperature and time (hours) to maximum germination. Analysis indicated the maximum germination across all temperatures: Georgia‐14N (HO) 50.5 h < Georgia Greener (NO) 53.2 h < Tifguard (NO) 54.4 h < Georgia‐07W (NO) 54.6 h < Georgia‐13M (HO) 56.5 h < Georgia‐06G (NO) 58.9 h < Georiga‐09B (HO) 60.4 h < Florida‐07 (HO) 67.8 h < FloRun 107 (HO) 69.7 h < Georgia‐12Y (NO) 72.0 h. Peanut cultivar vigor varied by year with respect to overall GDDs to reach Germ80 and maximum germination ( b 0 ). Overall vigor was similar for HO and NO runner‐type peanut cultivars. Peanut seed were consistent in germination, Germ80, and b 0 among the 10 evaluated cultivars over the 6 yr of testing. Core Ideas: Thermal gradient testing can be used for peanut seed germination. High oleic and normal oleic peanut cultivars exhibited stability in germination‐related variables. High oleic and normal oleic cultivars may exhibit phenotypic variation, but genotypic consistency.